Volume effect and exertional dyspnoea after bronchodilator in patients with COPD with and without expiratory flow limitation at rest. Issue 6 (1st June 2002) - Boni, E; Corda, L; Franchini, D; Chiroli, P; Damiani, G P; Pini, L; Grassi, V; Tantucci, C
Abstract : Background: A study was undertaken to investigate whether bronchodilators are associated with less breathlessness at rest and during light exercise in patients with moderate to severe chronic obstructive pulmonary disease (COPD) with resting tidal expiratory flow limitation (EFL; flow limited (FL)) compared with those without EFL (non-flow limited (NFL)). Methods: Twenty subjects (13 men) of mean (SD) age 65 (8) years (range 43–77) suffering from COPD with forced expiratory volume in 1 second (FEV1 ) 47 (18)% predicted were studied before and after inhalation of salbutamol (400 μg). Routine pulmonary function tests were performed in the seated position at rest. EFL was assessed by the negative expiratory pressure (NEP) method and changes in end expiratory lung volume (EELV) were inferred from variations in inspiratory capacity (IC). Dyspnoea was measured using the Borg scale at rest and at the end of a 6 minute steady state exercise test at 33% of the maximal predicted workload. Results: EFL occurred in 11 patients. Following salbutamol IC did not change in NFL patients but increased by 24% (95% CI 15 to 33) in FL patients (p<0.001). Maximal inspiratory pressure (Pi max) improved at EELV from 45 (95% CI 26 to 63) to 55 (95% CI 31 to 79) cm H2 O (p<0.05) in FL patients after salbutamol but remained unchanged in NFL patients. The workload performed during exercise amounted to 34 (95% CI 27 to 41) and 31 (95% CI 21 to 40) watts (NS) for patients without and with EFL, respectively. After salbutamol, dyspnoea did not change either at rest or during exercise in the NFL patients, but decreased from 0.3 (95% CI –0.1 to 0.8) to 0.1 (95% CI –0.1 to 0.4) at rest (NS) and from 3.7 (95% CI 1.7 to 5.7) to 2.6 (95% CI 1.1 to 4.0) at the end of exercise (p<0.01) in FL patients. Conclusions: Patients with COPD with EFL may experience less breathlessness after a bronchodilator, at least during light exercise, than those without EFL. This beneficial effect, which is closely related to an increase in IC at rest, occurs even in the absence of a significant improvement in FEV1 and is associated with a greater Pi max.